2000
DOI: 10.1259/bjr.73.865.10721317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bone mineral density and quantitative ultrasound of the calcaneus: site-matched correlation and discrimination of axial BMD status.

Abstract: The performance of quantitative ultrasound (QUS) and dual energy X-ray absorptiometry (DXA) bone densitometry of the calcaneus have been compared, both in terms of site-matched correlation and their discriminatory ability to identify osteoporotic and osteoporotic or osteopenic subjects. 91 female subjects (aged 56.9 +/- 9.6 years, 31-84 years) who were routinely referred for axial BMD assessment of the lumbar spine and femoral neck by DXA (Lunar DPX-L), consented to have additional measurements of QUS (McCue C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 11 publications
4
34
0
1
Order By: Relevance
“…In our study it was found that the mean T scores obtained by QUS at the initiation and 6 months were statistically comparable to those by DXA scan of the spine in both study and control groups. This is in accordance with other studies (7)(8).The increased bone turnover resulting from post-menopausal estrogen deficiency can be assessed by measuring serum and/ or urine biochemical markers of bone turnover (9). There is also now excellent evidence that the level of bone turnover is as strong a predictor of future fractures as is the level of BMD (10).…”
Section: Resultssupporting
confidence: 85%
“…In our study it was found that the mean T scores obtained by QUS at the initiation and 6 months were statistically comparable to those by DXA scan of the spine in both study and control groups. This is in accordance with other studies (7)(8).The increased bone turnover resulting from post-menopausal estrogen deficiency can be assessed by measuring serum and/ or urine biochemical markers of bone turnover (9). There is also now excellent evidence that the level of bone turnover is as strong a predictor of future fractures as is the level of BMD (10).…”
Section: Resultssupporting
confidence: 85%
“…Hip BMC demonstrated the strongest correlation with QUS, probably due to the trabecular-rich nature of the hip region (26) as well as calcaneus. In addition and similar to Rawal et al (23) and Wang et al (38), our data showed that SOS was poorly correlated with DXA measurements (r = .15), in part perhaps because SOS is a volumetric parameter, while DXA variables are areal parameters (14). In any case, the fact that significant associations between 2 measures of the same parameter were observed does not imply concordance or does not prevent from clinical misclassification.…”
Section: Discussionsupporting
confidence: 86%
“…Because of the heterogeneity of the calcaneus, an even higher correlation is observed if the region of BMD calculation is matched to that of QUS. 27 Unfortunately, in this study we did not match the region of the QUS to the BMD measurement. It is worth noting also that only moderate correlations have been reported between calcaneal and axial BMD.…”
Section: Correlationsmentioning
confidence: 97%